Neural correlates of causal attribution in negative events of depressed patients: Evidence from an fMRI study. Issue 7 (July 2015) - Hao, Lei; Yang, Junyi; Wang, Yanqiu; Zhang, Songyan; Xie, Peng; Luo, Qinghua; Ren, Gaoping; Qiu, Jiang
Highlights Depressed patients showed balanced attribution style versus controls. The inferior parietal lobe (IPL) showed a greater activation in patients versus controls for the non-self-serving in negative events. The duration of illness of patients was correlated with a BOLD signal change of the IPL.